UNLOCKING THE POTENTIAL OF MATARAM'S SOUTH SEA PEARL INDUSTRY FOR SUSTAINABLE GROWTH - Windiasari, Titin; Rosmiati; Ajeng Khalifatun Wardani , Lale; Ridho Hidayat , Ahmad (ShariaBiz International Journal of Economics & Business, 2025)
The South Sea pearl industry in Mataram is a vital component of the region's creative economy, contributing to local livelihoods and economic growth. Despite its potential, the industry faces challenges such as limited technological adoption, inadequate branding strategies, and fragmented regulatory support, which hinder its global competitiveness and investment appeal. This study aims to analyze the dynamics of the pearl industry in Mataram and propose strategies for sustainable growth and investment. A descriptive qualitative methodology was employed, utilizing secondary data from academic literature, government reports, and market analyses. The findings highlight the critical role of technological innovation, strategic branding, regulatory reforms, and socio-economic inclusion in enhancing the industry’s performance. The integration of the pearl industry with the tourism sector is identified as a key opportunity for diversification and increased revenue generation. The study underscores the importance of adopting modern production techniques, digital marketing strategies, and inclusive policies to unlock the industry's potential. These insights offer valuable guidance for stakeholders and policymakers, positioning the South Sea pearl industry in Mataram as a model for sustainable development in creative economies. Future research should focus on primary data collection and innovative practices to further advance the field.